Cyberbullying Among School Adolescents in an Urban Setting of a Developing Country: Experience, Coping Strategies, and Mediating Effects of Different Support on Psychological Well-Being - Ngo, Anh Toan; Tran, Anh Quynh; Tran, Bach Xuan; Nguyen, Long Hoang; Hoang, Men Thi; Nguyen, Trang Huyen Thi; Doan, Linh Phuong; Vu, Giang Thu; Nguyen, Tu Huu; Do, Hoa Thi; Latkin, Carl A.; Ho, Roger C. M.; et al. (Frontiers in Psychology, 2021)
Background: This study examined the cyberbullying experience and coping manners of adolescents in urban Vietnam, and explored the mediating effect of different support to the associations between cyberbullying and mental health issues. Methods: A cross-sectional study was performed on 484 students at four secondary schools. Cyberbullying experience, coping strategies, psychological problems and family, peer and teacher support were obtained. Structural Equation Modeling was utilized to determine mediating effects of different support on associations between cyberbullying and psychological problems. Results: 11.6% and 28.3% of students reported that they experienced and observed at least one cyberbullying act in the last three months, respectively. Among victims, only 48.2% tried to stop the perpetrators. Meanwhile, the majority of observers belonged to the “Intervene” group who tried to report cyberbullying acts or help victims. Family support was found to partially mediate associations between cyberbullying experience and observation with levels of psychological problems among adolescents. Conclusion: The 3-month rate of cyberbullying experience and observation among urban adolescents aged 11-14 was low. However, current coping strategies against cyberbullying were not sufficient. Family support is an important factor that should be considered for designing interventions to mitigating the impacts of cyberbullying on the mental health of adolescents